Exploring the presence of the GPR126 single nucleotide polymorphism (rs536714306) in periodontal patients of European ancestry - Chatzopoulou, Eirini; Fanourakis, Galinos; Papanikolaou, Nikolaos; Chatzistamou, Ioulia; Dereka, Xanthippi; Vastardis, Heleni (BMC research notes, 2025)
Objective G protein-coupled receptor 126 ( GPR126 ) gene has been implicated as a potential susceptibility factor for aggressive periodontitis in Japanese patients. This study aimed to investigate the presence of the GPR126 [c.3086 G > A] (rs536714306) polymorphism in patients with periodontitis in a Greek population and periodontal cases of European ancestry. A total of 82 subjects were recruited: 53 patients periodontally compromised (P) and 29 healthy controls (H). GPR126 genotyping was performed using Sanger sequencing. Additionally, data from the Gene-Lifestyle Interactions in Dental Endpoints (GLIDE) consortium were included in this study. Results No variants (rs536714306) in the GPR126 gene were detected in any of the samples. The homozygous for the reference allele GG genotype was observed in 100% of participants across all groups examined. Absence of GPR126 [c.3086 G > A] polymorphism indicates no association with susceptibility to periodontitis in a Greek cohort and periodontally compromised cases of European ancestry. This is the first focused report evaluating the presence of this polymorphism in periodontitis patients in a European population. Further genome-wide studies in larger sample and diverse populations are warranted to fully elucidate the potential role of GPR126 polymorphisms in periodontal disease susceptibility.